Three Pairs of New Spirocyclic Alkaloid Enantiomers From the Marine-Derived Fungus Eurotium sp. SCSIO F452 - Zhong, Weimao; Wang, Junfeng; Wei, Xiaoyi; Fu, Tingdan; Chen, Yuchan; Zeng, Qi; Huang, Zhonghui; Huang, Xinan; Zhang, Weimin; Zhang, Si; Long, Lijuan; Wang, Fazuo (Frontiers in Chemistry, 2019)
Three pairs of new spirocyclic alkaloid enantiomers eurotinoids A–C (1–3), as well as a known biogenetically related racemate dihydrocryptoechinulin D (4) were isolated from a marine-derived fungus Eurotium sp. SCSIO F452. Their structures were determined by spectroscopic analyses and ECD calculations. Compounds 1 and 2 represent the first two “meta” products from a nonstereoselective [4 + 2] Diels-Alder cycloaddition presumably between diketopiperazine alkaloid and benzaldehyde derivative via a new head-to-tail coupling mode biosynthetically, while 3 and 4 were “ortho” products. Their enantiomers exhibited different antioxidative and cytotoxic activities. The modes of action were investigated by a preliminary molecular docking study.